Climate change-induced drought evolution over the past 50 years in the southern Chinese Loess Plateau. (December 2019) - Zhang, Shengnan; Wu, Yiping; Sivakumar, Bellie; Mu, Xingmin; Zhao, Fubo; Sun, Pengcheng; Sun, Yuzhu; Qiu, Linjing; Chen, Ji; Meng, Xianyong; Han, Jichang
Abstract: Understanding the spatiotemporal evolution of drought is vital for effective water resources management especially in arid and semi-arid regions and under climate change. In this study, we developed the Soil and Water Assessment Tool (SWAT)-based drought evaluation tool and used it to investigate the spatiotemporal change of drought and its driving factors over the past 50 years (1965–2014) in a typical semi-arid area, the Wei River Basin, in the Loess Plateau. The temporal trend analysis of precipitation showed an intensified hydrological cycle with a longer dry interval, and the substantially decreased wind speed resulted in a significant decrease in the evapotranspiration and a slight increase in the soil water content. The spatiotemporal analysis of drought identified the vulnerable areas and indicated that spring drought was exacerbating. Overall, this study can be informative and valuable for the drought assessment and disaster alleviation in the Loess Plateau area. Graphical abstract: Image 1 Highlights: A SWAT-based Drought Evaluation Tool was developed. The system was proved to be efficient in the spatiotemporal drought analysis. It helps analyze the key driving factors of drought evolution in large-scale areas. The most vulnerable areas that are prone to drought were identified.